2015
DOI: 10.5430/jnep.v5n10p98
|View full text |Cite
|
Sign up to set email alerts
|

Effect of subcutaneous sterile water injection at the lumbosacral region on labour back pain

Abstract: Objective: This study aimed to evaluate the effect of subcutaneous sterile water injection at the lumbosacral region on labour back pain. Methods: A quasi-experimental, pre/post test design was utilized to carry out this trial at the Labour and Delivery room, Mansoura University Hospital, Egypt. Sixty three primiparous in spontaneous active labour, indicated a low back pain ≥ 7 on numeric pain rating scale, and expected to have spontaneous vaginal delivery were included in this study as a one study group. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Studies conducted on the subcutaneous injections of sterilized distilled water confirm the reduction of pain severity 30 min after the intervention. [91025]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted on the subcutaneous injections of sterilized distilled water confirm the reduction of pain severity 30 min after the intervention. [91025]…”
Section: Discussionmentioning
confidence: 99%
“…reported that 10 min and 1, 2, and 3 h after the injection, pain intensity decreases 2.5°, 3.5°, 4.5°, and 5°, respectively. [25] Cui et al ., in their study, concluded that pain severity score on a VAS had decreased 10, 45, and 90 min, and 1 day after the treatment. [14] Cui et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether the tissue to be given sterile water injection will affect the targeted analgesic is another debated topic, and the majority of the studies focus on intradermal injections [11,13,21,22]. On the other hand, some study samples showed that subcutaneous sterile water injection was also effective in relieving low-back pain [18,[23][24][25]. The literature includes studies that compared sterile water injection and other nonpharmacological pain control methods, yet while one study found sterile water injection more effective than transcutaneous electrical nerve stimulation (TENS), another study found it more effective than acupuncture [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to evaluate not only the effects of the method on pregnant women's pain perception but also on satisfaction and labor experience [4]. However, while few studies in the literature were found to have investigated mothers' satisfaction with the technique, no studies were found to have investigated its effects on labor experiences [15,17,24,26,34]. For this reason, this study aimed to investigate the effect of intradermal sterile water injection on pain perceptions and labor experiences of women who experience low-back pain during labor.…”
Section: Introductionmentioning
confidence: 99%